2016
DOI: 10.1039/c6ta00114a
|View full text |Cite
|
Sign up to set email alerts
|

Symmetric pseudocapacitors based on molybdenum disulfide (MoS2)-modified carbon nanospheres: correlating physicochemistry and synergistic interaction on energy storage

Abstract: Flower-like MoS2 modified with carbon nanospheres (CNS) displays energy-storage capability when used as an aqueous symmetric pseudocapacitor.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
62
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 125 publications
(68 citation statements)
references
References 29 publications
1
62
0
Order By: Relevance
“…Whereas an obvious interior cavity with the shell thickness of ~150 nm is available in each MoS 2 /RGO hollow microsphere as disclosed by the TEM observations (Figure 3e,f), indicating the complete removal of SiO 2 template without the damage of hollow structure. Inset of Figure 3f presents a high-resolution TEM (HRTEM) image of a single random MoS 2 nanosheet anchored on a MoS 2 /RGO hollow microsphere, where the lattice fringes are clearly observable and the interplanar spacing is deduced to be 0.62 nm, corresponding to the (002) crystal plane of MoS 2 [17,28,29]. Additionally, contrastive bare MoS 2 microspheres were also hydrothermally fabricated in the presence of Na 2 MoO 4 , CS(NH 2 ) 2 and a small amount of HF.…”
Section: Resultsmentioning
confidence: 99%
“…Whereas an obvious interior cavity with the shell thickness of ~150 nm is available in each MoS 2 /RGO hollow microsphere as disclosed by the TEM observations (Figure 3e,f), indicating the complete removal of SiO 2 template without the damage of hollow structure. Inset of Figure 3f presents a high-resolution TEM (HRTEM) image of a single random MoS 2 nanosheet anchored on a MoS 2 /RGO hollow microsphere, where the lattice fringes are clearly observable and the interplanar spacing is deduced to be 0.62 nm, corresponding to the (002) crystal plane of MoS 2 [17,28,29]. Additionally, contrastive bare MoS 2 microspheres were also hydrothermally fabricated in the presence of Na 2 MoO 4 , CS(NH 2 ) 2 and a small amount of HF.…”
Section: Resultsmentioning
confidence: 99%
“…The produced compounds such as intermediate ternary Na x MoO y and Na x WO y [54][55][56] crystalline phase could form and condense on the substrates for subsequent sulfurization. At the beginning, these Na-containing particles which were similar to PTAS and PTCDA [57] seeds could provide nucleation sites on the substrate [58,59] and then were sulfurized into the oxi-chalcogenide nanoparticles encased in a fullerene like shell [53,60].…”
Section: Growth Of MXmentioning
confidence: 99%
“…In our previous work, 12 we reported how the presence of CNS is intrinsically linked to the pseudocapacitance of MoS 2 with flower-like and spherical morphologies. The previous study suggested that different morphologies give different physico-chemical properties.…”
mentioning
confidence: 99%
“…14 In the last three years, it is interesting to observe that MoS 2 has begun to attract interest even as full cell (2-electrode) configurations. 12,[15][16][17][18][19][20] The supercapacitor performance of MoS 2 has been compared to that of the carbon nanotubes (CNT) array electrodes. 6,21 Spherical morphology of the MoS 2 remains the most investigated morphology for supercapacitor application.…”
mentioning
confidence: 99%
See 1 more Smart Citation